Mapping of a Paleochannel Through a Geoelectric - Andrade, Paula Rayane Lopes de (2019)
This paper presents the results of a survey of electric resistivity along a stretch of the Sucuru River, in the vicinity of the Sumé city, in the Northeast region of Brazil. The goal is to map the occurrence of sediments saturated with water whose main paleochannel is a suitable feature for drilling water-producer wells. Two manual Auger coring surveys were made with pick up of sediment samples for petrophysical tests and record of six 2D lines of electric resistivity, applying multiple vertical electric soundings, which were interpolated to generate a 3D electrical resistivity model of that part of the river. The results show that the fine sediments tend to have low values of electrical resistivity (lower than 50 ohm.m), except on non-saturated region, while intervals with lithotypes of high grain sizes tend to present resistivity values between 50 and 200 ohm.m, except in regions of high porosity and high water saturation. In general, it is seen that there is an area with resistivity higher than 200 ohm.m at the top, which corresponds to the non-saturated sediments zone, and another at the base, which corresponds to the crystalline basement. The model allows someone to view, in addition to the main paleochannel, secondary channels, which hardly would be completely identified through a regular core drilling program.